Electromagnetic vector sensors - An, Delie (2013)
A vector sensor consists of three orthogonal dipoles and three orthogonally oriented loops. It measures direction of arrival (DOA). It measures all six components of incident electromagnetic wave; hence, all available degrees of freedom are exploited. It performs better than scalar array antennas in terms of accuracy. [3rd Award]